GAMBARAN MASYARAKAT TENTANG PENDIDIKAN SERTA KONTRIBUSINYA - Saragih, Fernando; Simbolon, Gallex (Education For All, 2023)
Education is something special in the eyes of society where education is one of the keys to developing human resources. Many views regarding education became the basis for developing this research. This research focuses on a quantitative approach using survey methods. This research was carried out using a questionnaire with 28 statements (16 questions focused on perceptions of PLS and 12 on interest in continuing education to higher education. Based on these results it can be concluded that there is a positive and significant influence between public perceptions about education and interest in continuing education at state universities.